2017
DOI: 10.1002/smll.201700776
|View full text |Cite
|
Sign up to set email alerts
|

The Genetic Heterogeneity among Different Mouse Strains Impacts the Lung Injury Potential of Multiwalled Carbon Nanotubes

Abstract: Genetic variation constitutes an important variable impacting the susceptibility to inhalable toxic substances and air pollutants, as reflected by epidemiological studies in humans and differences among animal strains. While multi-walled carbon nanotubes (MWCNTs) are capable of causing lung fibrosis in rodents, it is unclear to what extent the genetic variation in different mouse strains influence the outcome. We chose four inbred mouse strains, including C57Bl/6, Balb/c, NOD/ShiLtJ and A/J, to test the pro-fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1
1

Relationship

4
2

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 59 publications
0
8
0
Order By: Relevance
“…We have previously demonstrated for silica and carbonaceous nanomaterials that the in vitro profibrogenic responses in THP-1 and BEAS-2B cells largely reflect their ability to generate similar biomarker responses in the bronchoalveolar lavage fluid (BALF) of mice receiving oropharyngeal aspiration. [22,26,32] The C57BL/6 mice were used for exposure to S1, S3, S5 and S6 PM2.5 particles, which correspondence to low, medium and high response level of pro-inflammatory and profibrogenic effects in vitro. The mice were sacrificed at 21 days after the oropharyngeal inspiration of the PM2.5 particles.…”
Section: Exposure To Mouse Lung To Determine the Fibrogenic Potentialmentioning
confidence: 99%
“…We have previously demonstrated for silica and carbonaceous nanomaterials that the in vitro profibrogenic responses in THP-1 and BEAS-2B cells largely reflect their ability to generate similar biomarker responses in the bronchoalveolar lavage fluid (BALF) of mice receiving oropharyngeal aspiration. [22,26,32] The C57BL/6 mice were used for exposure to S1, S3, S5 and S6 PM2.5 particles, which correspondence to low, medium and high response level of pro-inflammatory and profibrogenic effects in vitro. The mice were sacrificed at 21 days after the oropharyngeal inspiration of the PM2.5 particles.…”
Section: Exposure To Mouse Lung To Determine the Fibrogenic Potentialmentioning
confidence: 99%
“…The third example is the work with the engineered carbonaceous nanomaterials (ECNs), which includes carbon nanotubes (CNTs), graphene and graphene oxides (GO) [20, 21, 106109]. These materials have intrinsic electrical and optical characteristics, as well as the capability to finely tune the physicochemical properties such as size, durability, and surface chemistry, facilitating them to be widely used in biomedical and electronics industry.…”
Section: Successful Case Studies Of Using Predictive Toxicology Pamentioning
confidence: 99%
“…In order to comprehensively compare tubes with different characteristics, it is necessary to develop predictive toxicology paradigms which could characterize and categorize CNTs, graphene, GO into the specific libraries based upon their unique properties, for example, CNTs of different synthesis methods, dispersal states, surface functionalization, and lengths, etc. [106109, 117]. The key characterization methods are listed in Table 1.…”
Section: Successful Case Studies Of Using Predictive Toxicology Pamentioning
confidence: 99%
“…While it is generally accepted that long and stiff (micrometer scale) carbon nanotubes (CNTs) are more toxic than shorter or tangled tubes (nanometer scale) tubes, the data are based on materials of heterogeneous composition, without attempts to purify tubes of the same length or develop a tube‐length series that is based on the same starting material . Moreover, although it has been shown that tubes longer than 10 µm could act like fibers, with the ability to induce frustrated phagocytosis, our own studies have shown that SWCNTs and multiwalled carbon nanotubes (MWCNTs) at length scales well below those that cause frustrated phagocytosis, can induce acute and chronic lung injury …”
Section: Introductionmentioning
confidence: 99%
“…This purification method also yields sufficient tube quantities for performance of structure‐activity analysis, which allows one to address the role of individual tube properties to biological outcome . One of our preferred study approaches to assessing SWCNT and MWCNT properties is to study their profibrogenic effects in pulmonary cell types and the lung . Many of these studies have demonstrated that the long aspect ratio of these materials, rather than fiber‐like dimensions, play a role in triggering lysosomal damage and IL‐1β release in macrophages, which synergize with the ability of these materials to induce transforming growth factor (TGF)‐β1 production in lung epithelial cells .…”
Section: Introductionmentioning
confidence: 99%